2012
DOI: 10.1371/journal.pone.0039637
|View full text |Cite
|
Sign up to set email alerts
|

Moving Just Like You: Motor Interference Depends on Similar Motility of Agent and Observer

Abstract: Recent findings in neuroscience suggest an overlap between brain regions involved in the execution of movement and perception of another’s movement. This so-called “action-perception coupling” is supposed to serve our ability to automatically infer the goals and intentions of others by internal simulation of their actions. A consequence of this coupling is motor interference (MI), the effect of movement observation on the trajectory of one’s own movement. Previous studies emphasized that various features of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 42 publications
3
33
1
Order By: Relevance
“…Our results are consistent with behavioral studies which demonstrate automatic imitation (Press, Bird, Flach, & Heyes, , , ) and motor interference (Kupferberg et al, ) during action observation of artificial agents. Also single unit data in monkeys showed that fronto‐parietal brain areas discriminate between goals (grasp to eat or grasp to replace), but there is little evidence that they discriminate between agents (Bonini et al, ; Fogassi et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with behavioral studies which demonstrate automatic imitation (Press, Bird, Flach, & Heyes, , , ) and motor interference (Kupferberg et al, ) during action observation of artificial agents. Also single unit data in monkeys showed that fronto‐parietal brain areas discriminate between goals (grasp to eat or grasp to replace), but there is little evidence that they discriminate between agents (Bonini et al, ; Fogassi et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In the object observation condition (duration: 10 s), subjects only observed these objects. An additional condition (duration: 10 s), “grasping a cylindrically shaped block”, was used in the analysis of a separate study (Kupferberg et al, ), so that altogether there were 4 conditions in the actions execution experiment.…”
Section: Methodsmentioning
confidence: 99%
“…While automatic imitation of robotic actions is smaller in absolute value compared to human actions, it is not completely absent, and several studies document automatic imitation of movements made by real and virtual full‐body humanoid robots, regardless of the presence of biological motion. A key factor driving automatic imitation appears to be the presence of human‐like joint configuration, and not human‐like motion per se . Interference effects of observed movements on executed movements are reported for both humanoid robot and mechanical robot arms, as long as the latter had human‐like joint configurations.…”
Section: Impact Of Artificial Agent's Visual Featuresmentioning
confidence: 99%
“…However, we assume that it is not so much the appearance but rather similar motility that accelerated interaction. This assumption is supported by our recent study on motor interference using the same robots [53]. The necessity of the morphological similarity of observed agent for easy prediction of its actions might be caused by the "simulation theory".…”
Section: Discussionmentioning
confidence: 77%
“…This theory states that individuals recognize each other's intentions and predict each other's actions by imagining themselves in the other's position, and simulating mental states (beliefs, desires, intentions) that they would possess if they were in the other's 'shoes' [54], [55]. This procedure reduces the possible range of actors, whose intentions the observer might be able to simulate, since for simulation the observed actor should have the same motor constraints and morphological features as the observer (the "like me" hypothesis [56], [53]). Since this assumption is to some extent true in a humanoid robot but not an industrial one, the simulation procedure might be effective for attributing goals to motor actions of JAST, but not of JAHIR.…”
Section: Discussionmentioning
confidence: 99%